Presentation of the Model for Co-evolution of Governance and the Development of Smart Transportation Technologies in Tehran Metropolis - Seiri Sabet, Shabnam; Saghafi, Fatemeh; Mohaghar, Ali; Mohammadi, Mehdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to present a model for the elements shaping the co-evolution of governance and the development of smart transportation technologies. Methodology: This study employed a qualitative approach. Initially, by reviewing the literature on governance and smart technologies, the key factors from existing models and studies were extracted using content analysis, resulting in 234 initial codes. In the second step, expert interviews and the content analysis of these interviews were used to refine and complete the codes. The sampling method for the interviews was both snowball and judgmental, and after 31 interviews, convergence was reached. Findings: From the combination of the codes, 35 themes were extracted and categorized into 11 groups, leading to the final model. The model was explained in a panel of experts and confirmed after necessary revisions. The findings showed that increasing the penetration of information and technology, the need for an integrated transportation system, information technology infrastructure, and modern technologies in the transportation industry, as well as legal and regulatory considerations, are important factors that, in the framework of the evolutionary process, align with the three principles of transparency, accountability, and participation in the good governance model, affecting both the market and smart technology. Conclusion: Good organizational governance is achieved through the interaction of all levels within an organization. This interaction requires coordination among various components within the organization, its stakeholders, and its overall strategy, such that if this coordination is fully realized, organizational success and performance improvement will occur.